(Un)teaching the 'datafied student subject': perspectives from an education-based masters in an English university. Issue 4 (18th May 2020) - Harrison, Michaela J.; Davies, C.; Bell, H.; Goodley, C.; Fox, S.; Downing, B.
ABSTRACT: That compulsory education is datafied is widely acknowledged. A significant body of literature illuminates the policy context and technologies that have given rise to what we now call datafication. Less research has focussed on the consequences of datafication on teachers and learners. In this paper, we offer a unique perspective of these consequences in relation to qualified, experienced teachers as learners on education-based masters courses. Working within a post-qualitative frame, we employ a lesser-known approach to research, 'conversation as methodology', in order to explore our experiences and develop our expertise as HE practitioners. Through conversation, we identify datafication as both affective and effective – it shapes and produces particular learning and teaching encounters and it also shapes and produces subjectivities. We suggest that for education-based masters courses, this is troublesome, and can result in a process of (un)teaching, as we challenge the values and practices on which a datafied education depends.